Adsorption of Antibiotic in Aqueous Solution by a Family of Zirconium-based Metal Organic Frameworks - Hong, Le Thi; Dao, Phan Thi; Dai, Trinh Xuan (VNU Journal of Science: Natural Sciences and Technology, 2026)
In this research, a family of Zirconium-based metal-organic framework, derivatives of UiO-66 (UiO-66-NO 2 và UiO-66-NH 2 ), was synthesized and applied to adsorption of antibiotic contaminants in aqueous solution. The materials were characterized by X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), nitrogen adsorption-desorption (BET), and scanning electron microscope (SEM). The adsorption abilities of the materials were investigated toward Tetracycline as a representative for antibiotics. Adsorption capacities of TC on UiO-66-NO 2 , and UiO-66-NH 2 were 46.08, and 33.90 mg/g, respectively. The pH significantly affected the TC adsorption of the materials. The kinetics of adsorption of TC on the materials were investigated, which were excellently fitted with pseudo-second-order. In addition, the recycle test exhibited that the adsorption ability was almost unchanged for four adsorption times. The results of the research were well discussed and explained.